Między idealizmem i naturalizmem. Jana Gnatowskiego i Józefa Kotarbińskiego dyskusja o modelu literatury i krytyki nowoczesnej - Jauksz, Marcin (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2023)
The book presents the debate on the meaning of realism and naturalism for European and Polish literature. Jan Gnatowski’s 1878 study O realizmie w literaturze nowoczesnej (On Realism in Modern Literature) is a fundamental, though marked worldview, analysis of French 19th c. novels – from Musset, through Balzac and Flaubert, up to Daudet and Zola. This conservative attempt at analysis met with strong opposition from the positivist camp – its chief proponent being Józef Kotarbiński, who in 1879 published the article Wstecznictwo w krytyce literackiej (Backwardness in Literary Criticism). This edition contains the complete reprint of these two texts together with a commentary that shows Gnatowski, although strong in his judgments, reads texts ideologically foreign to him carefully – even with a certain fascination. Kortabiński when defending realism’s right to exist, however, approaches these uncompromising stories with a marked distance.
Between Idealism and Naturalism. Jan Gnatowski and Józef Kotarbiński - a Polemic On the Model of Literature and Contemporary Literary Criticism